Oficinas en el aire - Matayoshi, Valeria
Se reseñan las oficinas de Airbnb alredeor del mundo.
Keywords: HENEGHAN PENG ARCHITECTS; PENG, HENEGHAN; GENSLER AND ASSOCIATES ARCHITECTS; BRASIL; DUBLIN; SAO PAULO; IRLANDA; ESTADOS UNIDOS; SAN FRANCISCO; PORTLAND; JAPON; TOKYO; DISEÑO DE INTERIORES; OFICINAS; MM18; BORA; SUPPOSE DESIGN OFFICE